The Effect of Physical Activity on Oxidative Stress in Inhibiting Systemic Aging - Thaniya Dianroosti; Ni Nyoman Ayu Dewi (International Journal Labs, 2026)
Systemic aging accelerated by oxidative stress is a global health challenge that demands evidence-based intervention strategies. Physical activity offers a promising non-pharmacological approach, but its molecular mechanisms require a review of the relevant literature. This article aims to analyze the molecular mechanisms underlying the effectiveness of physical activity in suppressing oxidative stress and inhibiting the systemic aging process. This literature review employs a systematic search of the PubMed, Scopus, Web of Science, and ScienceDirect databases to identify studies published between 2021 and 2025. Inclusion criteria encompassed studies analyzing the interaction between physical activity, oxidative stress, and biomarkers of aging. Synthesis of the results showed that physical exercise consistently increased expression of endogenous antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase) through activation of redox-sensitive transcription factors. Combination therapy with aerobic and resistance exercise effectively lowered lipid peroxidation biomarkers (malondialdehyde) and increased total antioxidant capacity. Significant clinical adaptations were achieved at an optimal intensity of 70-85% VO?max for 8-12 weeks, although individual responses showed heterogeneity influenced by genetic factors and baseline health status. The therapeutic effectiveness of physical exercise in combating aging—mediated by regulation of oxidative stress—has been consistently demonstrated in numerous studies. However, its application in clinical practice requires personalized interventions, with exercise programs individually tailored to ensure optimal therapeutic responses.